Case Report: Individualization of Intensive Transactional Analysis Psychotherapy on the Basis of Ego Strength - Messina, Irene; Scottà, Francesco; Marchi, Arianna; Benelli, Enrico; Grecucci, Alessandro; Sambin, Marco (Frontiers in Psychology, 2021)
In Intensive Transactional Analysis Psychotherapy (ITAP) intensity is obtained with both technical expedients and the relational manner with the patient. In ITAP, the therapist modulates pressure and support commensurately to patients Ego strength. In the present article, we contrast two clinical cases of young adults in which Ego strength produced different therapy outcome and process. We present excerpts of the psychotherapy process that illustrates technical aspects of ITAP therapy as well as therapist’s attitude that we describe as holding. We show quantitative therapy outcomes consisting in effects size values of changes in Clinical Outcome in Routine Evaluation‐Outcome Measure (CORE‐OM) scores in of Baseline, Treatment and Follow‐up phases, and qualitative outcome evaluated with the Change Interview at the end of the therapy. In the patient with high Ego strength we observed a rapid improvement and a complete recovery at the end of the therapy, whereas the results of the patient with low Ego strength were less consistent (more fluctuations in CORE-OM scores including deterioration, but good qualitative outcome). We conclude that quantitative and qualitative outcome data, together with process observations, are required to have a complete picture of therapy effectiveness. Moreover, we conclude that qualitative Ego strength is not a limitation for the use of expressive therapy such as ITAP, but rather it is an important variable that should be considered to dose confrontations and support.